DEFINITION csubst1_getl_ge()
TYPE =
∀i:nat
.∀n:nat.(le i n)→∀c1:C.∀c2:C.∀v:T.(csubst1 i v c1 c2)→∀e:C.(getl n c1 e)→(getl n c2 e)
BODY =
assume i: nat
assume n: nat
suppose H: le i n
assume c1: C
assume c2: C
assume v: T
suppose H0: csubst1 i v c1 c2
we proceed by induction on H0 to prove ∀e:C.(getl n c1 e)→(getl n c2 e)
case csubst1_refl : ⇒
the thesis becomes ∀e:C.(getl n c1 e)→(getl n c1 e)
assume e: C
suppose H1: getl n c1 e
consider H1
∀e:C.(getl n c1 e)→(getl n c1 e)
case csubst1_sing : c3:C H1:csubst0 i v c1 c3 ⇒
the thesis becomes ∀e:C.∀H2:(getl n c1 e).(getl n c3 e)
assume e: C
suppose H2: getl n c1 e
by (csubst0_getl_ge . . H . . . H1 . H2)
we proved getl n c3 e
∀e:C.∀H2:(getl n c1 e).(getl n c3 e)
we proved ∀e:C.(getl n c1 e)→(getl n c2 e)
we proved
∀i:nat
.∀n:nat.(le i n)→∀c1:C.∀c2:C.∀v:T.(csubst1 i v c1 c2)→∀e:C.(getl n c1 e)→(getl n c2 e)